2020
DOI: 10.1152/japplphysiol.00113.2019
|View full text |Cite
|
Sign up to set email alerts
|

The interactions between respiratory and cardiovascular systems in systolic heart failure

Abstract: Heart failure (HF) is a complex and multifaceted disease. The disease affects multiple organ systems, including the respiratory system. This review provides three unique examples illustrating how the cardiovascular and respiratory systems interrelate because of the pathology of HF. Specifically, these examples outline the impact of HF pathophysiology on 1) respiratory mechanics and the mechanical “cost” of breathing; 2) mechanical interactions of the heart and lungs; and on 3) abnormalities of pulmonary gas ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 96 publications
3
25
0
Order By: Relevance
“…Hence, fusion of E/A waves and e'/a' waves often occurs beyond heart rates of 100 bpm, thereby compromising the accuracy of this assessment. E and e' are also highly load dependent, which results in a large variability at peak exercise, when the increased respiratory rate induces shifts in preload and afterload ( 21 , 22 ). ExE/e' has a good positive predictive value for diagnosis of elevated exPAWP, but its negative predictive value (55–77%) allows a substantial amount of false negative results ( 12 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, fusion of E/A waves and e'/a' waves often occurs beyond heart rates of 100 bpm, thereby compromising the accuracy of this assessment. E and e' are also highly load dependent, which results in a large variability at peak exercise, when the increased respiratory rate induces shifts in preload and afterload ( 21 , 22 ). ExE/e' has a good positive predictive value for diagnosis of elevated exPAWP, but its negative predictive value (55–77%) allows a substantial amount of false negative results ( 12 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is to be assumed that breath-hold-to-breathing differences of parameters under expiratory breath-holding would be different, presumable smaller [41,42]. Patients with heart failure, valvular diseases and atrial fibrillation, arrhythmia or pulmonary diseases were not enrolled, and different results might have been found in these populations due to altered intrathoracal pressures [43][44][45]. Moreover, the average age in our study population was 58 years and breath-hold-induced changes might differ in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Wb and Pb are cornerstone metrics of dynamic respiratory mechanics, both of which have furthered our understanding of respiratory physiology during exercise in both health and disease. For example, by measuring the Wb and Pb during physical activity, investigators have demonstrated that: 1) the total and flow-resistive component of Pb are systematically higher in women than in men (1,2); 2) the total Pb during exercise is greater in older than in younger individuals (3)(4)(5); 3) the energy expended by respiratory muscles is an important contributor to the "slow component" of O 2 uptake kinetics during strenuous exercise (6); 4) the total Wb and Pb is elevated in patients with stable heart failure (7,8), chronic obstructive pulmonary disease (9,10), and interstitial lung disease (10); and 5) the Pb incurred during severe-to maximal-intensity exercise may be so large that it causes a redistribution of cardiac output away from exercising limbs toward the respiratory muscles, thereby curtailing exercise performance (11,12).…”
Section: Introductionmentioning
confidence: 99%